Design and simulation of a distribution STATCOM considering voltage sag mitigation and harmonic elimination - Abdul Wahab, Noor Izzri; Mariun, Norman; Mohamed, Azah; Mohibullah, (2002)
This paper describes the theory, design and simulation of a 12-pulse Distribution STATCOM on an llkV distribution system. The distribution STATCOM (D-STATCOM) is one of the custom power (CP) family Which also includes dynamic voltage restorer (DVR), solid state fault current limiter (SSFCL), active filters and solid state transfer switch (SSTS). Custom power offers customer with no power interruptions, tight voltage regulation, low harmonic voltage and acceptance of fluctuating and non-linear loads without effect on the terminal voltage. The D-STATCOM, which consists of a thyristor-based voltage source inverter, uses advanced power electronics to provide voltage stabilization, flicker suppression, power factor correction, harmonic control and a host of other power quality solutions for both utility and industrial applications. In this paper however, the concern will be mitigating Voltage sags on the llkV distribution system and reduction of harmonics generated by the device. The D-STATCOM Simulations are done by using the PSCAD/EMTDC version 3.0.7 electromagnetic transient program.